Taxonomy of ’Euconnus complex’. Part XIII. Status of Afrotropical subgenera of Euconnus: Cephaloconnus, Cerviconnus, Ursoconnus and Nodoconnus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Status of four Afrotropical subgenera of Euconnus Thomson is clarified. Examination of the type species of Cephaloconnus Franz, Cerviconnus Franz, Ursoconnus Franz and Nodoconnus Franz led to the following conclusions: i) Cephaloconnus and Cerviconnus are placed as junior synonyms of Napochus Thomson; ii) Ursoconnus is placed as a junior synonym of Euconophron Reitter; iii) Nodoconnus is maintained as a valid name and a subgenus of Euconnus. An emended diagnosis and redescription of Nodoconnus is given, and the lectotype is designated for its type species, Euconnus gomyanus Franz.